Internet Based Infertility Information in Bahasa Indonesia Quality Survey - Hestiantoro, Andon; Kusumaningtyas, Intan (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To assess the quality of websites providing informationon infertility and its management in Bahasa.Methods: Differences between website types and affiliates wereassessed for the credibility, accuracy and ease of navigation usingpredefined criteria. We used Google search engine with the keyword